Celebrating Applied Sciences Reaches 20,000 Articles Milestone Feature Papers in Applied Biosciences and Bioengineering Section - Cappello, Francesco; Gorska-Ponikowska, Magdalena (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
To celebrate the publication of 20,000 articles in Applied Sciences, we launched this Special Issue "Celebrating Applied Sciences Reaching Its 20,000 Article Milestone: Feature Papers of the Applied Biosciences and Bioengineering Section". We have invited well-known experts in different areas of interest covered in "Applied Biosciences and Bioengineering" to submit their original research papers and review articles of the highest quality in celebrating together with our readers on this special occasion. This Special Issue has collected more than 10 papers featuring important and recent developments or achievements in biosciences and bioengineering, with a special emphasis on recently discovered techniques or applications.